Nitrous anhydrase activity of carbonic anhydrase II: cysteine is required for nitric oxide (NO) dependent phosphorylation of VASP in human platelets - Dimitrios Tsikas; Stepan Gambaryan (Taylor & Francis Group, 2021)
The carbonic anhydrase (CA) family does not only catalyse the reversible hydration of CO2 to bicarbonate, but it also possesses esterase and phosphatase activity. Recently, bovine CA II and human CA II have been reported to convert inorganic nitrite (O=N-O−) to nitric oxide (NO) and nitrous anhydride (N2O3). Given the ability of NO to mediate vasodilation and inhibit platelet aggregation, this CA II activity would represent a bioactivation of nitrite. There are contradictory reports in the literature and the physiological role of CA II nitrite bioactivation is still disputed. Here, we provide new experimental data in support of the nitrous anhydrase activity of CA II and the key role L-cysteine in the bioactivation of nitrite by CA II. Using washed human platelets and by measuring VASP phosphorylation we provide evidence that exogenous nitrite (10 µM) is bioactivated to NO in a manner strongly depending on L-cysteine (100 and 200 µM). The process is not inhibitable by acetazolamide, a potent CA inhibitor. The contradictory results of recently published studies in this area are thoroughly discussed.